Manajemen Media Digital Berbasis Artificial Intelligence dan Minat Belajar Mahasiswa - Herlambang, Susatyo; Subiyantoro, Ary (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this study is to research how students' interest in learning about the digital age is influenced by digital media based on artificial intelligence (AI) at the Yogyakarta Administrative Management Academy (AMAYO) in Yogyakarta. Quantitative approaches are used in this research methodology. Purposive sampling strategies were utilized to get data from 75 pupils. The study tool was a questionnaire, and the data was evaluated using the validity test, reliability test, linear regression, T-test, F-test, and coefficient of determination (R²) in SPSS 26. This study suggests that digital media based on artificial intelligence (AI) has a favorable effect on students' interest in learning, with a regression coefficient of 0.920. Because the t-test yields a calculated t value of 57.031, which is greater than the t-table value of 1.666, H₀ is rejected and Ha is accepted. This suggests that students' interest in studying in the digital age at AMAYO Yogyakarta is significantly impacted by the use of digital media based on artificial intelligence (AI). The computed F value of 3252.522, which is higher than the F table of 3.97, indicates that the F-test also reveals results that need serious consideration. Additionally, the 97.8% coefficient of determination (R2) suggests that digital media based on artificial intelligence (AI) can affect students' motivation in learning, whereas 2.2% is influenced by other elements that are not within the purview of this study. According to the study's findings, AMAYO Yogyakarta students can boost their interest in learning in the digital age by utilizing digital media powered by artificial intelligence (AI).